Description of the rare localization of Dirofilaria repens in human in the right inguinal lymph node - Larisa Ermakova; Sergey Nagorny; Igor Kornienko; Julia Kiosova; Sergey Todorov; Natalia Pshenichnaya; Ainash Kuandykova (IDCases, 2021)
D. repens is the causative agent of subcutaneous dirofilariasis in canine animals. In recent years, human invasion by this vector-borne helminthiasis has been recorded in many countries with temperate climate, but the localization of this helminth in the cavities of the human body is extremely rare. Cases of atypical localization of D. repens are described in the organs of the chest, cervical lymph node, in the spermatic cord and epididymis. It is usually requires differential diagnosis with neoplastic or metastatic processes. We report a case of the detection of Dirofilaria repens in the right inguinal lymph node in a 56-year-old woman. Helminth was identified by parasitological and molecular biological methods. A morphological study of cross sections of the nematode in histological preparations and molecular biological method, the polymerase chain reaction (PCR) of scrapings of histological material, were used in parallel.